THE INFLUENCE OF WORK ENVIRONMENT, JOB CONFLICT, WORK LOAD AND COMPENSATION ON UPTD EMPLOYEE PERFORMANCE WULUHAN HEALTH CENTER - Faisal, Amien; Azhad, M. Naely; Rusdiyanto, Rusdiyanto (Universitas Muhammadiyah Tangerang, 2024)
The work environment encompasses various elements around employees that can affect their job performance. This includes physical factors such as room layout, lighting, and temperature, as well as non-physical elements like social interactions, work atmosphere, and company policies. If these elements are neglected, it can lead to disruptions in employee performance. Conversely, a supportive work environment can enhance motivation and enthusiasm, leading to increased efficiency and productivity. A pleasant work environment can create a calm atmosphere while working, while adequate facilities play a crucial role in improving performance. This study aims to thoroughly evaluate how various factors, such as the work environment conditions, conflicts, workload, and compensation, affect employee performance at Puskesmas Wuluhan. To achieve this objective, a causality method was applied involving 76 respondents selected through a saturation sampling technique, ensuring that all relevant members of the population were included in the sample. The results of multiple linear regression analysis reveal that both the work environment and compensation have a significant impact on employee performance, indicating that improvements in these aspects can substantially enhance performance. Conversely, the study found that conflicts and workload do not have a significant effect on employee performance at Puskesmas Wuluhan, suggesting that these factors may have less influence on performance compared to the work environment and compensation.